Speed has no correlation to muscle volume of hip flexors and tibialis anterior muscles in Division l football athletes - Guymon, I. B.; Wilwand, M.; Allen, S. P.; Mortensen, B. B.; Johnson, A. W. (International Journal of Exercise Science Conference Proceedings, 2025)
In American football (AF) a desirable trait is sprint speed that leads to success such as increased touchdowns, yards gained, and number of sacks. Researchers suggest training programs can improve an athletes` sprint speed. Considering the swing to stance phases, the hip flexors (HF) and tibialis anterior (TA) may impact an athletes` speed. The HF initiates the swing phase, while the TA muscle dorsiflexes the foot allowing the toes to clear the ground.